2021
DOI: 10.3390/ph14060593
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of N-Acetylcysteine on the Rat Mesocorticolimbic Pathway: Role of mGluR5 Receptors and Interaction with Ethanol

Abstract: N-acetylcysteine (NAC) is a prodrug that is marketed as a mucolytic agent and used for the treatment of acetaminophen overdose. Over the last few decades, evidence has been gathered that suggests the potential use of NAC as a new pharmacotherapy for alcohol use disorder (AUD), although its mechanism of action is already being debated. In this paper, we set out to assess both the potential involvement of the glutamate metabotropic receptors (mGluR) in the possible dual effect of NAC administered at two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Probiotics are a simple and readily available complementary intervention that is involved in the development, growth and maturation of multiple systems, and many diseases have been shown to havea strong association with probiotics, For example, irritable bowel syndrome [41] 、Metabolic syndrome [42] 、Allergic diseases [43] etc, And probiotics have a positive effect on neurological development, cognitivefunction, behavior and emotional regulation [44] . A growing number of studies have shown that for infants and young children experiencing early life stressful events, the addition of probiotics from breast milk to formula mimics to some extent the nutritional supply of breast milk to infants and young children to achieve healthy growth [45,46] .…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are a simple and readily available complementary intervention that is involved in the development, growth and maturation of multiple systems, and many diseases have been shown to havea strong association with probiotics, For example, irritable bowel syndrome [41] 、Metabolic syndrome [42] 、Allergic diseases [43] etc, And probiotics have a positive effect on neurological development, cognitivefunction, behavior and emotional regulation [44] . A growing number of studies have shown that for infants and young children experiencing early life stressful events, the addition of probiotics from breast milk to formula mimics to some extent the nutritional supply of breast milk to infants and young children to achieve healthy growth [45,46] .…”
Section: Discussionmentioning
confidence: 99%